The conditions and level of ICT integration in Malaysian Smart Schools. - Wan Ali, Wan Zah; Mohd Nor, Hajar; Hamzah, Azimi; Alwi, Hayati (International Journal of Education and Development using ICT, 2009)
This qualitative study attempts to describe the conditions that facilitated the implementation of Information Communication Technology (ICT) integration in the Malaysian Smart School and the problems that emerge during the process of integration. A total of twenty-one informants were interviewed. Based on data analysis two sets of conditions were revealed. They were the essential conditions and the supporting conditions. The findings also revealed that teachers in this study employed four levels of approaches in integrating ICT in the schools. Time, course content and technical malfunction were found to be the main problems that the teachers faced during this process.